The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.immuni.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering and Reversing Tumor Immune Suppression

Abstract: Generating an anti-tumor immune response is a multi-step process that is executed by effector T cells that can recognize and kill tumor targets. However, tumors employ multiple strategies to attenuate the effectiveness of T cell-mediated attack. This is achieved by interfering with nearly every step required for effective immunity, from deregulation of antigen-presenting cells, to establishment of a physical barrier at the vasculature that prevents homing of effector tumor-rejecting cells, and through the supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
428
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(436 citation statements)
references
References 174 publications
(214 reference statements)
4
428
0
4
Order By: Relevance
“…Moreover, TAM favor the local recruitment of Treg cells by secreting CCL22. 9 We have previously reported that the CD115 ligands M-CSF and IL-34, drive monocytes into IL-10 high IL-12 low immunoregulatory macrophages which are similar to ovarian cancer TAM. 5,10,11 They represent a robust model to decipher in vitro the biology of immunoregulatory macrophages.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, TAM favor the local recruitment of Treg cells by secreting CCL22. 9 We have previously reported that the CD115 ligands M-CSF and IL-34, drive monocytes into IL-10 high IL-12 low immunoregulatory macrophages which are similar to ovarian cancer TAM. 5,10,11 They represent a robust model to decipher in vitro the biology of immunoregulatory macrophages.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, tumor-mediated suppression of immune responses, regulated by various immunosuppressive cell types such as myeloid-derived suppressor cells and regulatory T cells (T regs ) that reside in the tumor microenvironment, could potentially limit the therapeutic benefits of DC-based immunotherapy [22,23]. Therefore, the impact of cancer vaccines can only truly be evaluated when all these different players are taken into account.…”
Section: Therapeutic Vaccinations With Mrna-sonoporated Dcsmentioning
confidence: 99%
“…This in turn leads to hypoxia and lowering of the microenvironment pH, which further promotes tumor progression. At the same time hypo-perfusion and hypoxia compromise normal immune response, thus rendering the tumor impervious to the immune system [11,12] with an invasive and metastatic phenotype [13]. As expected, reduced blood supply also interferes with effective drug delivery to the tumor [9].…”
Section: Causes Of Insufficient Drug Delivery To Tumorsmentioning
confidence: 79%